Non-invasive measurement of biomechanical skin properties in systemic sclerosis. Issue 3 (1st March 2002) - Balbir-Gurman, A; Denton, C P; Nichols, B; Knight, C J; Nahir, A M; Martin, G; Black, C M
Abstract : Objective: To evaluate biomechanical properties of skin in patients with systemic sclerosis (SSc) using the BTC-2000 suction device. Methods: Twenty five patients with limited cutaneous SSc (lcSSc), 20 patients with diffuse disease (dcSSc), and 25 age matched healthy controls were evaluated. Viscoelastic deformation (VED, mm), elastic deformation (ED, mm), ultimate deformation (UD, mm), and pressure-deformation ratio (PDR, mm Hg/mm) were measured on the dorsal surface of the forearm, shoulder, and above the trapezius muscle on the back. Results: Indices of skin extensibility (VED, ED, UD) were reduced and resistance to stress (PDR) increased in patients with dcSSc compared with healthy controls, or patients with lcSSc, at all three sites (p<0.001). At all sites, and overall, UD, ED, and VED were lower and PDR was higher at skin score above grade 2, compared with clinically normal skin. For both lcSSc and dcSSc biomechanical differences from controls were found even at sites of clinically normal skin. Conclusion: BTC-2000 is a sensitive tool for clinical evaluation of skin involvement in SSc and may be a valuable adjunct to skin sclerosis score in disease monitoring.